Gender and Feminism in an Islamic Perspective - Lazuardi, Fakhrul; Shamsu, Lilly Suzana binti Haji (FOCUS, 2024)
The great dominance of men in various areas of life and the injustice felt by Western women had an impact on the emergence of the feminist movement, which initially only demanded equal rights to continue education in all aspects, including gender equality. This study uses a literature review method on writings that talk about Islam and Feminism. From the research results, it was found that in Islam, the roles of men and women in terms of politics, economics, education, social life and legal sanctions have the same portions and responsibilities. Islamic texts urge the progress and role of women in various areas of good life.